Delayed allograft inflammation following alemtuzumab induction for kidney transplantation. (8th August 2013) - Heilman, Raymond L.; Khamash, Hasan A.; Smith, Maxwell L.; Chakkera, Harini A.; Moss, Adyr A.; Reddy, Kunam S.
Abstract Background In a recent clinical trial in kidney transplant recipients, induction with alemtuzumab and rabbit‐antithymocyte globulin (r‐ATG) was equally effective in preventing rejection during the first post‐transplant year; however, this study did not include protocol biopsies. Methods The aim of this study was to analyze the impact of alemtuzumab induction on rejection and subclinical inflammation during the first post‐transplant year compared with a historic control group receiving induction with r‐ATG. All patients received tacrolimus and mycophenolate mofetil (MMF). Results There were 361 in the alemtuzumab group and 478 in the r‐ATG groups. Rejection (excluding Banff borderline), during the first year, occurred in 14% of the alemtuzumab group and 9% of the r‐ATG group (p = 0.03). Estimated glomerular filtration rate (GFR) (chronic kidney disease (CKD)‐EPI formula) at one yr and graft survival at three yr were similar. On the protocol biopsies, interstitial inflammation (Banff i scores) and tubulitis (Banff t scores) were more likely in the r‐ATG group at one month, but at four and 12 months, both inflammation and tubulitis were more likely in the alemtuzumab group. Conclusions We conclude that alemtuzumab induction is associated with delayed inflammation at four and 12 months, but this inflammation did not appear to negatively impact the GFR or graft survival.